Muslimness as a political formation: an inquiry into Muslim presence. (2nd January 2020) - Sulaiman, Mohammed
ABSTRACT: In this article, I undertake an investigation into the political significance of Islam and Muslimness. By doing so, I aim to underscore the primacy of Islam's ontological (constitutive) nature and its irreducibility to any of its ontic (empirical) articulations. This project necessitates the recovery of the political as the moment of the formation of a collective order and community, irreducible to any of its material expressions (e.g. territorial or institutional unity). Thus, the article renounces the objectivity of the secular grammar which fixes, essentializes, and reduces Muslimness to being merely 'religious' as opposed to 'political'. By contrast, it attempts to retrieve Islam's basic condition of existence and hence emancipate it from the confines of the Western epistemic structure. Toward that end, the article presents a deconstructive analysis of Islam as an autonomous universe of meaning inaugurated by the event of the Divine Revelation to Prophet Muhammad as its originary moment. By doing so, I also emphasize the primacy of Muslimness as a political subjectivity, whose unity and autonomy is contingent upon the drawing of its most universal boundaries and the exclusion of an outside – a function, I argue, which had historically been fulfilled by the mechanism of the caliphate. Finally, the article discusses an alternative conceptualization of diaspora in order to come to grips with the political implications of Muslimness in the post-caliphate world order.